Innovative counseling model based on mindfulness and cognitive-behavioral harmony to foster comfort and happiness in learning - Lestari, Luh Putu Sri; Gading, I Ketut; Antara, Putu Aditya (Indonesian Journal of Educational Development (IJED), 2025)
Improving students’ comfort and happiness in learning is essential to fostering a more engaged and effective educational experience. However, conventional teaching approaches often neglect the integration of psychological well-being strategies, limiting students’ ability to enjoy and immerse themselves in the learning process fully. The sample size was determined using the Slovin formula, and a cluster random sampling technique was employed to ensure a balanced representation across rural, suburban, and urban schools of students divided into experimental and control groups. Data were collected using comfort and happiness questionnaires designed to measure emotional and cognitive responses to learning environments. The data were analyzed using multivariate analysis of variance (MANOVA) to evaluate the impact of the MCBH intervention. The findings reveal that students who participated in the MCBH-based intervention experienced significantly higher levels of comfort and happiness compared to those in the control group. The integration of mindfulness practices with cognitive-behavioral strategies helped students regulate emotions, reduce anxiety, and cultivate positive learning experiences. These results suggest that the MCBH framework can effectively enhance students’ emotional well-being, contributing to a more supportive and enjoyable learning atmosphere. The study highlights the importance of embedding holistic psychological approaches into education to promote not only academic success but also personal growth and emotional resilience.